SELF-IDENTITIY IN THE POEM “F? BAYTI UMM?” BY MAHMOUD DARWISH (FERDINAND DE SAUSSURE’S SEMIOTICS) - Nadzif Aulia Rohmah; Mugy Nugraha; Siti Robiatul Adawiyah; Annisa Khoirunni'mah; Safina Nurul Aulia (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study aims to analyze the construction of self-identity in Mahmoud Darwish’s poem F? Bayti Umm? through Ferdinand de Saussure’s structural semiotic framework. The research employs a qualitative descriptive method with textual analysis to examine how identity is represented through internal dialogue, memories of the past, personal transformation, and reflective consciousness. The analysis applies the concepts of signifier-signified relations as well as syntagmatic and paradigmatic structures to interpret the emergence of identity within the poetic text. The findings reveal that the lyrical subject’s identity is not presented as a fixed or singular entity, but as a dynamic process continuously negotiated through language, memory, and lived experience. Fragmented expressions, reflective questioning, symbolic diction, and conscious self-positioning illustrate shifts in life orientation and the ongoing pursuit of self-understanding. The novelty of this study lies in its systematic integration of Saussurean structural semiotics to demonstrate how poetic language actively constructs identity rather than merely reflecting it. These findings contribute to contemporary literary and humanities research by offering a structured semiotic model for interpreting identity representation in poetry and by providing theoretical implications for interdisciplinary studies of language, literature, and cultural identity formation.